Komunikasi Antarbudaya Masyarakat Pendatang Di Pulau Sebatik Perbatasan Indonesia-Malaysia - Muhammad Hairul Saleh; Muh Harliman Saleh; Ignasius Dwi Oktavianus (Fakultas Ilmu Komunikasi UKWMS, 2023)
This study on intercultural communication of migrant communities on Sebatik Island on the Indonesia-Malaysia border examines communication practices between Javanese, Bugis, and Timorese migrants. Using a qualitative approach and collecting data from in-depth interviews and participatory observations, the study found that the process of intercultural communication is created through economic and cultural arenas. Communication in the Javanese economic arena with the Bugis can be seen from the businesses carried out together, such as culinary, hospitality, supermarket businesses and at the same time recruiting Javanese and Bugis as employees of their businesses. In the cultural arena, intercultural communication can be seen from the phenomenon of intermarriage which allows the creation of perceptual similarities between them. Communication in the Timorese economic arena with the Bugis is seen in the vegetable business network which is the main source of income for the Timorese and the recruitment of Timorese as assistants in the Bugis household. Communication in the cultural arena between Timorese and Bugis is also seen in terms of mixed marriages as well as between Javanese and Bugis. Through the economic and cultural arena, there is a change in the mindset of some people which has implications for the creation of a more dynamic and harmonious community condition in the context of communication of border communities with various differences in culture, customs, languages, and religions.ABSTRAK Studi ini tentang komunikasi antarbudaya masyarakat pendatang di Pulau Sebatik perbatasan Indonesia-Malaysia yang mengkaji praktek komunikasi antara pendatang Jawa, Bugis, dan Timor. Dengan menggunakan pendekatan kualitatif dan mengumpulkan data dari hasil wawancara mendalam dan observasi partisipasi, studi ini menemukan bahwa proses komunikasi antarbudaya, tercipta melalui arena ekonomi dan budaya. Komunikasi dalam arena ekonomi orang Jawa dengan Bugis terlihat dari bisnis yang dilakoni secara bersama, misalnya bisnis kuliner, perhotelan, supermarket dan sekaligus merekrut orang Jawa dan Bugis sebagai karyawan dari bisnis mereka. Dalam arena budaya, komunikasi antarbudaya terlihat dari fenomena perkawinan campuran yang memungkinkan terciptanya persamaan persepsi di antara mereka. Adapun komunikasi dalam arena ekonomi orang Timor dengan Bugis terlihat pada jaringan bisnis sayur-sayuran yang menjadi sumber penghasilan utama orang Timor dan perekrutan orang Timor sebagai asisten dalam rumah tangga orang Bugis. Komunikasi dalam arena budaya antara orang Timor dengan Bugis juga terlihat dalam hal perkawinan campuran sebagaimana yang terjadi juga antara orang Jawa dengan Bugis. Melalui arena ekonomi dan budaya, terjadi perubahan pola pikir sebagian masyarakat yang berimplikasi pada terciptanya suatu kondisi masyarakat yang lebih dinamis dan harmonis dalam konteks komunikasi masyarakat perbatasan dengan berbagai perbedaan budaya, adat, Bahasa, dan agama.